(untitled) (The International Journal for Scientific Research, 2026)
The principle of good faith is a fundamental principle of modern contractual relations. It aims to achieve contractual justice and balance between contracting parties by obligating them to honesty, integrity, and cooperation in fulfilling their contractual obligations. The importance of this principle is increasing in light of the rapid development of civil transactions and the growing complexity of contractual relationships. This necessitates legal protection to prevent the abuse of rights and ensure stability in transactions. The problem addressed in this study is the effectiveness of the principle of good faith in the execution of civil contracts within the Saudi legal system, the extent to which its regulatory framework aligns with the provisions of Islamic jurisprudence, and its legal implications in addressing breaches of contractual obligations. The study aims to analyze the concept of good faith and its legal and Sharia foundations, demonstrate its applications during contract execution, and reveal the legal consequences of violating it. It also examines recent judicial trends in the Kingdom of Saudi Arabia related to this principle. The study adopted a descriptive-analytical approach by analyzing the regulatory texts contained in the Saudi Civil Transactions Law, in addition to a comparative approach to identify points of agreement and disagreement between the Saudi system and Islamic jurisprudence. Modern judicial applications were also utilized to highlight the practical applications of the principle. The study concluded that the principle of good faith constitutes a governing rule for the execution of civil contracts in the Saudi system, and that its foundation is derived from the provisions of Islamic Sharia, which emphasizes fulfilling contracts and prohibits fraud, deception, and harming others. It also showed that the Saudi Civil Transactions Law has strengthened the scope of application of this principle, making it a standard for interpreting and executing contractual obligations. Furthermore, the Saudi judiciary has moved towards enshrining its practical effects by protecting the party acting in good faith, preventing the abuse of rights, and establishing compensation when harm results from bad faith. The study recommended the necessity of developing judicial applications related to the principle of good faith, enhancing legal awareness of its importance in contractual relationships, and conducting further applied studies on its role in modern contracts and electronic contracts. This would contribute to strengthening contractual security, achieving justice, and ensuring the stability of transactions in the Kingdom of Saudi Arabia.